Influencia del consumo de sustancias psicoactivas en el desarrollo de habilidades sociales del adolescente. - Guerrero Villagómez, Adriana Isabel (2023)
ABSTRACT: This research project consists of a bibliographical review whose main objective is to determine the influence of the consumption of psychoactive substances on the development of adolescent social skills. This research has a quantitative approach and is bibliographical, cross-sectional, and descriptive. The methodological process was carried out from the search for investigative background in different sources of information; 24 scientific documents were chosen, primarily articles, through inclusion criteria and methodological quality (CRF-QS), which allowed select valuable studies that support current research. The results indicate that the consumption of psychoactive substances in recent years has increased considerably due to different individual, social, and family factors; the most consumed substance is alcohol, followed by tobacco and marijuana, drugs that people currently have greater access to; this issue has become a problem worldwide and directly affects the proper development of adolescents who present more challenging to communicate, express emotions, control impulses and relate to others. These aspects refer to social skills, characteristics learned mainly in the family environment and can be affected by various factors.